1975
DOI: 10.1002/bjs.1800620405
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic change in duplications of the alimentary tract

Abstract: Two cases of adenocarcinoma arising in sequestrated duplications of the bowel in adults are reported. The literature is reviewed and a tendency for duplications to present in early childhood is noted. Although relatively few of these anomalies persist into adult life 8 cases of neoplastic change have now been reported. The histological features of many of the duplications undergoing malignant degeneration suggest the presence of underlying epithelial instability in this condition. It is postulated that duplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
4

Year Published

1977
1977
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 15 publications
1
59
0
4
Order By: Relevance
“…Although these lesions are usually benign, surgical resection is the most feasible method of treatment in order to prevent future complications: massive hemorrhage, cystic infection, short bowel Sy, mass effect obstruction and rarely cancerous degeneration [11]. Malignant degeneration (adenocarcinomas) has been reported in patients with untreated rectal duplications, by Ballantyne in 1932 [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although these lesions are usually benign, surgical resection is the most feasible method of treatment in order to prevent future complications: massive hemorrhage, cystic infection, short bowel Sy, mass effect obstruction and rarely cancerous degeneration [11]. Malignant degeneration (adenocarcinomas) has been reported in patients with untreated rectal duplications, by Ballantyne in 1932 [12].…”
Section: Discussionmentioning
confidence: 99%
“…A possible case of carcinoma in a sigmoid colon duplication was recorded in 1882 by Lockwood and an adenomatous polyp in a double colon has also been described (Van Zwalenburg 1952). Orr & Edwards (1975) reviewed the reported cases of malignant change in duplications of the alimentary tract and described two of their own, two out of seven adenocarcinomas arising in a presacral cystic duplication. Recently Downing et al (1978) have reported an mvasive adenocarcinoma in a rectal duplication which was treated by abdominoperineal excision of the rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel duplications should be completely excised whenever possible, because ectopic gastric mucosa may be present [5], and because of the potential risk for subsequent malignant transformation [9]. However, they tend to be paramesenteric, sharing a common muscular wall, although each has its own mucosal lining [10].…”
Section: Discussionmentioning
confidence: 99%